Patient-Reported Outcomes with Selpercatinib Among Patients with RET Fusion–Positive Non-Small Cell Lung Cancer in the Phase I/II LIBRETTO-001 Trial. (30th September 2021) - Minchom, Anna; Tan, Aaron C; Massarelli, Erminia; Subbiah, Vivek; Boni, Valentina; Robinson, Bruce; Wirth, Lori J; Hess, Lisa M; Jen, Min-Hua; Kherani, Jennifer; Olek, Elizabeth; McCoach, Caroline E
Abstract: Background: LIBRETTO-001 is an ongoing, global, open-label, phase I/II study of selpercatinib in patients with advanced or metastatic solid tumors. We report interim patient-reported outcomes in patients with RET fusion–positive non-small cell lung cancer (NSCLC). Patients and Methods: Patients completed the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (QLQ-C30) version 3.0 at baseline (cycle 1, day 1), approximately every other 28-day cycle until cycle 13, and every 12 weeks thereafter. Data were evaluated through cycle 13 as few patients had reached later time points. A change of ≥10 points from baseline in domain scores was considered clinically meaningful. Results: Among 253 selpercatinib-treated patients, 239 were categorized into subgroups by prior therapy: treatment-naïve ( n = 39), one prior line of therapy ( n = 64), or two or more prior lines of therapy ( n = 136). The QLQ-C30 was completed by >85% of patients at each time point. Most patients overall and in each subgroup maintained or improved in all health-related quality of life (HRQoL) domains during treatment. The percentage of patients who experienced clinically meaningful improvements ranged from 61.1% to 66.7% for global health status, 33.3% to 61.1% for dyspnea, and 46.2% to 63.0% for pain. The 61.1% of patients with improved dyspnea had two or more prior lines of therapy; median time to first improvement was 3.4 months. At the first postbaseline evaluation (cycle 3), 45.9% of all patients reported a ≥10-point reduction in pain. Conclusion: In this interim analysis, the majority of patients with RET fusion–positive NSCLC remained stable or improved on all QLQ-C30 subscales at each study visit, demonstrating favorable HRQoL as measured by the QLQ-C30 during treatment with selpercatinib. Abstract : An objective of the LIBRETTO-001 trial was to describe patient-reported outcomes during selpercatinib treatment. This interim analysis summarizes findings in patients with RET fusion-positive non-small cell lung cancer.